Temperate Deciduous Trees in a Changing World: Their Phenology and Interactions - da Fonseca Alecrim, Evelyn (Université d'Ottawa | University of Ottawa, 2025)
This thesis examines the ecological interactions within temperate deciduous forests, focusing on wild bees, trees, and understorey herbs, and how these species respond to climate change. In my first data chapter, using pan traps, I sampled bees in both the canopy and understorey of a temperate deciduous forest biweekly from early spring to mid-summer of 2021. My findings reveal that forest canopies are crucial yet often overlooked habitats for wild bees. A significant number of ground-nesting bees were found foraging in the canopy, with arboreal pollen, particularly from Quercus and Acer species, forming a substantial part of their diet. This suggests that excluding the canopy from bee community studies could lead to underestimating bee populations and overlooking key aspects of their foraging behaviour. In my second data chapter, I analyzed 13 years of phenological data for 10 tree species and 11 springflowering forest herbs across 965 sites in northeastern North America, collected by citizen scientists under the USA-National Phenology Network. Contrary to expectations, the data showed that spring-flowering herbs advance their phenology more rapidly than trees in response to warming, particularly at middle and higher latitudes. This faster response may allow these herbs to extend their growing season and increase carbon uptake as temperatures rise. However, the variation in responses across latitudes and species highlights the complexities involved in predicting long-term ecological impacts. Additionally, in my final data chapter, I investigated the temperature sensitivity of phenology in temperate tree species across Europe using leaf-out data from the Pan-European Phenology Project (PEP725) and climate data from the European Climate Assessment & Dataset (E-OBS). My analysis focused on the relationship between chilling accumulation and heating accumulations (CA-HR response rate) and how this relationship varies with local environmental conditions. The results indicate that populations in warmer, drier, and lower-elevation areas have weaker phenological responses to warming, while those in colder, wetter, and higher-elevation areas have stronger phenological responses to warming. This variation suggests that local adaptation significantly influences how different populations respond to climate change.
Keywords: Phenology; wild bees; plant-plant interactions; climate change